Worldchanging, revised & updated : a user's guide for the 21st century - Bluestone, Carissa, ....-; McKibben, Bill, ....-; Steffen, Alex, ....- (New York (N.Y.) : Abrams, 2011)
Five years after the initial publication of Worldchanging, the landscape of environmentalism and sustainability has changed dramatically. The average reader is now well-versed--even inundated--with green lifestyle advice. In 2011, green is the starting point, not the destination. This second edition of the bestselling book is extensively revised to include the latest trends, technologies, and solutions in sustainable living. More than 160 new entries include up-to-the-minute information on the locavore movement, carbon-neutral homes, novel transportation solutions, the growing trend of ecotourism, the concept of food justice, and much more.
Includes bibliographical references and index.
Keywords: Environmentalism; Sustainable development; Green movement